Lower Nr5a2 Level Downregulates the β-Catenin and TCF-4 Expression in Caerulein-Induced Pancreatic Inflammation - Sun, Ya Mei; Zheng, Shuai; Chen, Xue; Gao, Feng; Zhang, Jie (Frontiers in Physiology, 2020)
Nuclear receptor subfamily 5 group A member 2 (Nr5a2) is widely involved in the physiological and pathological processes of the pancreas. However, the cytological and molecular evidence regarding how Nr5a2 implicated in acute pancreatitis (AP) remains insufficient. Here, we explored this problem by using cellular AP model in both normal and Nr5a2 silenced AR42J pancreatic acinar cells. An in vitro cellular model of AP was established by stimulating AR42J cells with caerulein (CAE) for 24 h. Reduced Nr5a2 expression was observed in the CAE-treated cells. Nr5a2 silencing led to AP-like inflammation, with increased interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α mRNA levels. In the cellular AP model, Nr5a2 silencing further increased IL-1β, IL-6 and TNF-α mRNA levels, as well as amylase activity. In addition, we found that Nr5a2 silencing did not affect IL-10 level under physiological conditions but inhibited the anti-inflammatory response of IL-10 in AP model. Moreover, in CAE-induced pancreatic inflammation, Nr5a2 silencing increased the apoptosis and necrosis of acinar cells and inhibited the proliferation of acinar cells, which has not been shown previously. Further experiments showed, for the first time, that Nr5a2 silencing downregulated the expression of β-catenin and its downstream target gene T cell factor (TCF)-4 in the cellular AP model but increased the expression of nuclear factor (NF)-κB. In conclusion, in CAE-induced pancreatic inflammation, lower Nr5a2 level leads to downregulation of β-catenin and its downstream target gene TCF-4 and upregulation of NF-κB, which exacerbates the inflammatory response and cell damage and inhibits the proliferation and regeneration of acinar cells.